Valoración medioambiental de los niveles de asimilación de la Riviera Mexicana: homogeneidad geográfica y heterogeneidad económica - Sánchez Crispín, Álvaro; Propin Frejomil, Enrique (Observatorio Medioambiental, 1999)
This paper presenís a syntheíic image of the population and economy of the Mexican Riviera, a portion of the Mexican coast eomprising from Puerto Vallaca to Bahías de Huatulco. The final research eartographic product is a map showing llie levels of economie assimilation for this pan of Mexico, that contribules significantly to the understanding of recent tourism expansion in West and South Mexico, particularly in places such as Acapulco and Puerto Vallarta.